2022
DOI: 10.3390/lubricants10080179
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Analysis of Dual Membrane Restrictor for Hydrostatic Bearing

Abstract: In this paper, a dual membrane restrictor design was proposed to improve the stiffness performance of the compensated hydrostatic bearing. Theoretical models for the proposed dual membrane restrictors were derived. Analysis of these models showed that a high stiffness region could be achieved at the desired loading region through the proper selection of the design parameters. A series of simulations were conducted to study the variations in the design parameters on the stiffness and clearance variations. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They also serve as a safety element that helps to align the surfaces using the pressure difference they generate. There are various types, from basic, such as orifice (see [19,20] or [21]), to more sophisticated, including membranes [22] or controllable elements, such as electromagnetic valves [23,24]. Previous research aimed to compensate for pad misalignment using compliant support numerically [25,26] and experimentally [27], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They also serve as a safety element that helps to align the surfaces using the pressure difference they generate. There are various types, from basic, such as orifice (see [19,20] or [21]), to more sophisticated, including membranes [22] or controllable elements, such as electromagnetic valves [23,24]. Previous research aimed to compensate for pad misalignment using compliant support numerically [25,26] and experimentally [27], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [8] proposed a dual-membrane restrictor design to improve the stiffness performance of the compensated hydrostatic bearing. They derived theoretical models for the proposed dual-membrane restrictors and found that the membrane stiffness in the inlet restrictor was the most dominant parameter for the performance of the compensated bearing system.…”
mentioning
confidence: 99%